Cellular behavior in embryogenic and non-embryogenic sugar beet calluses - Moghaddam, B.E.; Taha, R.M. (2005)
The present study discusses the results of cytological studies of two kinds of sugar beet callus, i.e., embryogenic and non-embryogenic tissues. The calluses were produced through culture of secondary leaves on Murashige and Skoog medium containing two hormone combinations. One week after transfer of calluses onto fresh medium, their cells were viewed using electron microscopy and an image analyzer. Observations showed that cells of the two callus types had considerable differences in cell structure and various organelles. Of note were the high amount of polyploidization, rough endoplasmic reticulum, polysome, poly-nucleolus, and incomplete cell wall together with abnormal partitioning in non-embryogenic cells, as compared to embryogenic cells. In contrast, vacuolation of cytoplasm, perfect cell wall and partitioning structure, and the high proportion of nucleus/cytoplasm area were recognized in embryogenic cells.